Pengetahuan - Ghaniyannisa, Aura Wahyu; Supariasa, I Dewa Nyoman; Hadisuyitno, Juin; Setyobudi, Sugeng Iwan (NUTRITURE JOURNAL, 2023)
Abstract Background: The problem of malnutrition is one of the nutritional problems being faced by countries in the world, including Indonesia. The problem of malnutrition can be caused by a lack of nutritional intake and infectious diseases. Objective: The purpose of this study was to determine differences in students' knowledge and attitudes before and after counseling on balanced nutrition with animation video media in fourth graders students at SDN Sukun 2 Malang City. Design: This type of research is a experimental study using a pre-experimental research design with One Group Pretest Posttest type. This research was conducted in May 2023 at SDN Sukun 2 Malang City. The sampling technique used was purposive sampling with a total sample of 40 students. Results: The mean value of student knowledge before and after balanced nutrition training using animated video media each is 30 and 55.75. The mean value of students' attitudes before and after balanced nutritional training is 58.93 and 67.56. The result of the Paired Sample T-Test showed that there are significant differences in knowledge (p-value=0,000) and attitudes (p-value=0,000) of the students before and after counseling on balanced nutrition with animation video media. Conclusions: There are significant differences in knowledge and attitudes of the students before and after counseling on balanced nutrition with animation video media. Keywords: Knowledge; Attitude; Counseling; Balanced Nutrition; Video Animation